DEVELOPMENT OF PHYTOPLANKTON MODEL WITH APPLICATION TO SONGKHLA LAKE, THAILAND - S. Suwanidcharoen; W. Liengcharernsit (Lowland Technology International, 2012)
In this study, mathematical models are developed for simulating phytoplankton and nutrients dispersions in a water body. Two-dimensional vertically average mass balance equations of salinity, nitrogen and phosphorus in various forms and phytoplankton nitrogen are used as governing equations. The finite element method with Galerkin’s weighted residual technique is used in model formulation. The developed models are applied to Songkhla Lake, which is one of the most important water resources in the south of Thailand, where algal bloom problem occurs in some months almost every year. Data on nutrient loadings from various sources in the watershed area are estimated based on the existing land use patterns, population density, livestock, aquaculture, and farming activities. Data on water depth and current velocities are obtained from a hydrodynamic model. The results from the model are illustrated to show distribution patterns of salinity, various forms of nitrogen and phosphorus, as well as phytoplankton nitrogen. The developed models can be used as a tool for assessing the effect of nutrient loading on algal bloom phenomena and are useful for water quality management planning of this lake and other water bodies.